Sistem Informasi E-Disposisi Surat Berbasis Web pada Kantor Camat Tungkal Jaya Kabupaten Musi Banyuasin - Rohmawati, Ema; Yulianingsih, Evi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to create an e-disposition letter information system application, improve the efficiency of letter management, facilitate access and tracking of letters, so as to improve the quality of public administration services. The method used is Rapid Application Development (RAD), the results of which research developed a web-based letter e-disposition information system for the Tungkal Jaya Sub-District Office, Musi Banyuasin Regency. This system is designed to improve the efficiency of letter management by reducing the use of paper, accelerating the flow of disposition, and facilitating real-time monitoring of letter status, this system has been tested and proven to be able to help various actors involved, such as admins, employees, secretaries, and leaders in managing incoming and outgoing letters more effectively. The implementation of this system is expected to support the digitalisation of government administration and improve the quality of public services in the sub-district office.